Afro-Colombian Women’s Organisations in Post- Accord Colombia: Gendering and Racialising Violent Pluralism across the Conflict Continuum in Bogotá, Colombia (Alternautas, 2022)
This article will examine the mobilisation strategies of two groups of Afro-Colombian women now living in Bogotá – AFROMUPAZ and the Colectiva Matamba – in order to add an intersectional dimension to growing calls for ongoing theories on the gender of violent pluralism. Indeed, by recognising and addressing the specific ways in which Afro-Colombian women experience violence because of their positions in society, we will be able to better understand the strategies they continue to employ in an attempt to obtain guarantees on their rights as citizens, as victims, and as women.